2016
DOI: 10.1016/j.scienta.2015.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hairy roots by Agrobacterium rhizogenes -mediated transformation of spine gourd ( Momordica dioica Roxb. ex. willd) for the assessment of phenolic compounds and biological activities

Abstract: a b s t r a c tAn efficient protocol for hairy root induction of spine gourd (Momordica dioica) was established using Agrobacterium rhizogenes (KCTC 2703). This study evaluates the phenolic compound production, antioxidant and antimicrobial (antibacterial, antifungal and antiviral) activities of transgenic hairy root cultures in M. dioica . Hairy roots were induced from leaves, petiole, and internodal explants. Molecular analysis of PCR and gene sequencing using specific primers of rolC and aux1 revealed T-DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…Among the sucrose concentrations, the highest biomass of roots was found in media accompanied with 30 g L −1 sucrose (1.8 g DW) and then with 20 g L −1 sucrose (1.34 g DW) (Figure ). In agreement with our results, optimal carbon source concentration was reported to be 30 g L −1 for hairy root growth of other plant species . Beside the effect of sucrose concentration on plant growth, sucrose is also known to have an influence on the yield of secondary products .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Among the sucrose concentrations, the highest biomass of roots was found in media accompanied with 30 g L −1 sucrose (1.8 g DW) and then with 20 g L −1 sucrose (1.34 g DW) (Figure ). In agreement with our results, optimal carbon source concentration was reported to be 30 g L −1 for hairy root growth of other plant species . Beside the effect of sucrose concentration on plant growth, sucrose is also known to have an influence on the yield of secondary products .…”
Section: Resultssupporting
confidence: 91%
“…Our result confirms preceding reports designated that bacterial strains and type of explants significantly influenced the generation of transgenic roots . The diverse responses of different plant tissues to A. rhizogenes ‐mediated transformation have been formerly described . The differences in morphology and growth rate of hairy roots could be explained by the diversity of plasmids of the A. rhizogenesis strains and differences in the virulence potential of distinct strains.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, among these systems, Agrobacteriummediated gene transfer has been widely studied as a strategy for producing hairy root lines with high yield for bioactive compounds 6 . Genetically transformed hairy roots established by using the transformation of a plant cell with A. rhizogenes offer a promising system for secondary metabolite production due to their inherent genetic and biochemical stability 7 . Yield enrichment approach involving the exogenous addition of elicitor molecules is one of the most promising ways employed to enhance the productivity of phytochemicals in in vitro cultures 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously it has been reported that elicitation of hairy root cultures and improvement in biosynthetic competence in vitro were reported 10,11,12 . The involvement of natural phytohormones, such as jasmonic acid (JA) and salicylic acid (SA) in signal transduction cascades has led to the use of these molecules as exogenous inducers of defense mechanisms for boosting accumulation of various secondary metabolites in some plant in vitro systems 7 . Several findings on the production of many variable secondary metabolites using JA and SA elicitors in hairy root cultures of various medicinal plants 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%